Childhood lung function and the association with β2‐adrenergic receptor haplotypes. (29th March 2013) - Torjussen, Tale M; Munthe‐Kaas, Monica C; Mowinckel, Petter; Carlsen, Kai‐Håkon; Undlien, Dag E; Lødrup Carlsen, Karin C
Abstract: Aim: To determine associations between ADRB2 polymorphisms and lung function through childhood, and possible modification by gender, pet keeping or tobacco smoke. Methods: Four ADRB2 single nucleotide polymorphisms (rs1042711, rs1042713, rs1042714 and rs1800888) were genotyped in 953 children from the prospective birth cohort 'Environment and Childhood Asthma' study and analysed for association with flow‐volume parameters at birth (tidal breathing) and at 10 years of age (maximally forced), stratified by environmental exposures. Results: The risk of reduced lung function was reduced in 10‐year‐old children carrying the most common ADRB2 haplotype (CGGC) (OR 0.45 (95% CI 0.25, 0.82)), whereas there was no association between lung function at birth and ADRB2 haplotypes. Tobacco smoke exposure, gender and pet keeping did not significantly interact with the haplotypes in influencing lung function. Conclusion: This study demonstrates a possible protective effect by the ADRB2 haplotype I (CGGC) on reduced FEV1 in 10‐year‐old children, whereas no ADRB2 geno‐/haplotypes were significantly associated with neonatal lung function. The ADRB2 gene thus appears to contribute to lung function development in childhood, independently of smoking, pets and gender. Abstract :